U.S. trends in antiretroviral therapy use, HIV RNA plasma viral loads, and CD4 T-lymphocyte cell counts among HIV-infected persons, 2000 to 2008. - Althoff, Keri N; Buchacz, Kate; Hall, H Irene; Zhang, Jinbing; Hanna, David B; Rebeiro, Peter; Gange, Stephen J; Moore, Richard D; Kitahata, Mari M; Gebo, Kelly A; Martin, Jeffrey; Justice, Amy C; et al. (Annals of internal medicine, 2012)
The U.S. National HIV/AIDS Strategy targets for 2015 include "increasing access to care and improving health outcomes for persons living with HIV in the United States" (PLWH-US).
Keywords: Adolescent; Adult; Aged; Anti-Retroviral Agents; CD4 Lymphocyte Count; Cross-Sectional Studies; Drug Prescriptions; Epidemics; Female; HIV Infections; HIV-1; Humans; Male; Middle Aged; Population Surveillance; Prospective Studies; RNA, Viral; United States; Viral Load; Young Adult